In-situ analyses of carbonaceous matter in manganiferous black shales: Analytical proxies and implication for ore processing. (15th August 2018) - Orberger, B.; Delarue, V.; Rodriguez, C.; Salaün, A.; Wallmach, T.; Wirth, R.; Boussafir, M.; Dreux, G.; Lafon, S.; Schreiber, A.
Highlights: We propose an approach to estimate the carbonaceous matter related to minerals compared to free carbonaceous matter (interstitial to grains). This approach is innovative and provide a simple tool to developing and optimizing beneficiation of metal rich (Au, Pb, Zn, Cu, Mn…) black shales. We established a method to analyse carbonaceous matter by QEMSCAN at grain size > 5 µm. Abstract: Carbonaceous matter is generally known to be problematic for metal recovery during metallurgical processing of black shales. In particularly, metal upgrading during beneficiation prior to (bio-) hydrometallurgical and/or pyrometallurgical processing is hindered by the presence of abundant carbonaceous matter (CM). This study presents the characterization of CM and mineral bound carbonaceous matter (CMP) in three manganese carbonate-rich shales hosting 6–8 wt% total organic carbon. Non-destructive methods, such as incident light microscopy, scanning electron (SEM) and focused-ion-beam-transmission electron microscopy (FIB-TEM), QEMSCAN and electron microprobe, were used to show that free CM is adsorbed onto illite-smectite surfaces. This form of CM ranges in grain size from sub-micrometer up to ≈100 μm. The most efficient method to show the illite-smectite association is SEM and for quantification of this association, QEMSCAN should be used. Mineral-bound carbonaceous matter may be relicts of extrapolymers (pyrite and/or carbonate) and needs characterization using FIB-TEM. The quantity of CM can then be estimated by a rough calculation as the difference between the total organic carbon (Rock Eval) and the free carbon calculated from normative mineral compositions based on X-ray Fluorescence (XRF) and X-ray-Diffraction (XRD) analyses. The mineral bound CM could not be detected by QEMSCAN under conventional analytical conditions. We estimated that about 85% of the CM in the test samples was adsorbed on mineral surfaces and about 15% was bound to minerals. The physical protection of the CM by clays, and the morphological and density differences between pyrite, carbonates and biochemically-bound CM in pyrite/carbonates needs to be taken into consideration in the process design.